Mitochondrial Fission-Mediated Lung Development in Newborn Rats With Hyperoxia-Induced Bronchopulmonary Dysplasia With Pulmonary Hypertension - Dai, Yuanyuan; Yu, Binyuan; Ai, Danyang; Yuan, Lin; Wang, Xinye; Huo, Ran; Fu, Xiaoqin; Chen, Shangqin; Chen, Chao (Frontiers in Pediatrics, 2021)
Background: Bronchopulmonary dysplasia (BPD) is the most common chronic respiratory disease in premature infants. Oxygen inhalation and mechanical ventilation are common treatments, which can cause hyperoxia-induced lung injury, but the underlying mechanism is not yet understood. Mitochondrial fission is essential for mitochondrial homeostasis. The objective of this study was to determine whether mitochondrial fission (dynamin-related protein 1, Drp1) is an important mediator of hyperoxia lung injury in rats. Methods: The animal model of BPD was induced with high oxygen (80–85% O2). Pulmonary histological changes were observed by hematoxylin-eosin (HE) staining. Pulmonary microvessels were observed by immunofluorescence staining of von Willebrand Factor (vWF). Protein expression levels of Drp1 and p-Drp1 (Ser616) were observed using Western Blot. We used echocardiography to measure pulmonary artery acceleration time (PAT), pulmonary vascular resistance index (PVRi), peak flow velocity of the pulmonary artery (PFVP), pulmonary arteriovenous diameter, and pulmonary vein peak velocity. Mitochondrial division inhibitor-1 (Mdivi-1) was used as an inhibitor of Drp1, and administered through intraperitoneal injection (25 mg/kg). Results: Pulmonary artery resistance of the hyperoxide-induced neonatal rat model of BPD increased after it entered normoxic convalescence. During the critical stage of alveolar development in neonatal rats exposed to high oxygen levels for an extended period, the expression and phosphorylation of Drp1 increased in lung tissues. When Drp1 expression was inhibited, small pulmonary vessel development improved and PH was relieved. Conclusion: Our study shows that excessive mitochondrial fission is an important mediator of hyperoxia-induced pulmonary vascular injury, and inhibition of mitochondrial fission may be a useful treatment for hyperoxia-induced related pulmonary diseases.